Patterns of Care for Adolescent With Schizophrenia: A Delphi-Based Consensus Study - Vita, Antonio; Barlati, Stefano; Bellomo, Antonello; Poli, Paolo Fusar; Masi, Gabriele; Nobili, Lino; Serafini, Gianluca; Zuddas, Alessandro; Vicari, Stefano (Frontiers in Psychiatry, 2022)
Background: The current conceptualization of schizophrenia as neurodevelopmental disorder should lead to innovative public health policies in terms of a reorganization of the mental health care systems, particularly in the transition from adolescence to adulthood, to reduce personal, familiar, and social costs and burdens. The purpose of the project was to perform a survey among a panel of Italian schizophrenia experts, to share evidence-based information on adolescent schizophrenia and explore the degree of consensus among professionals in the following four macro-areas: early diagnosis; pharmacological treatment; health care system organization and transition process from adolescent to adulthood; and psychosocial interventions. Methods: The consensus process consisted of a two-step web-based Delphi method, which took place between June and November 2021. The survey was developed by a panel of four psychiatrists and four child neuropsychiatrists, identified as key opinion leaders (KOLs). The KOLs identified 21 statements involving a total of 70 items with a major need of clarification on early-onset schizophrenia (EOS). The survey was distributed to 86 specialists in psychiatry and child neuropsychiatry. Results: The results revealed a large agreement among the expert group on all the investigated areas of adolescent schizophrenia patterns of care and management. Consensus was ultimately reached for 67 items of the Delphi survey (95.7%), while negative consensus was reached for 2 items and no consensus was reached for 1 item. Conclusions: Overall, results showed a significant gap between the acquired scientific knowledge and clinical practice. In this scenario, it should be necessary to plan specific initiatives at a multiple level, to edit recommendations on clinical decision-making, as well as to prompt changes at the political and organizational levels, also involving scientific societies, patients, and family associations, to overcome the barriers that delay the implementation process.